Development and validation of the Salt Intake-Related Knowledge, Attitude, and Practice Questionnaire for Malaysian adults. - Zainal Arifen, Zainorain Natasha; Ngoh Wan Hwah; Hng Jie Wei; Siti Aishah Ismail; Fairuzam, Maryam Hanis; Haron, Hasnah (Malaysian Journal of Nutrition, 2024)
Introduction: Malaysian adults consume excessive amounts of salt daily, which could lead to hypertension. Understanding knowledge, attitudes, and practices (KAP) surrounding salt intake is crucial for designing effective interventions to reduce excessive consumption and its associated health risks. Therefore, this study aimed to adapt an existing salt intake-related KAP questionnaire that was previously employed in a local population-based survey and to validate and test its reliability. Methods: This cross-sectional study comprised two phases: (1) adaptation, content validation (CV), and face validation (FV); (2) pilot testing and reliability testing. CV and FV involved a total of seven experts and ten Malaysian adults from the Klang Valley, respectively. Pilot testing involved 139 Malaysian adults to determine the questionnaire's reliability. Content validity index (CVI) and Face validity index (FVI) values were calculated to analyse CV and FV. Reliability of each domain was analysed by obtaining Cronbach's alpha (a) values. Results: A self-administered questionnaire comprising six items each for knowledge, attitude, and practice was developed. The questionnaire demonstrated acceptable item-level CVI (I-CVI) and item-level FVI (I-FVI) values of at least 0.83, indicating that the items were relevant, clear, non-ambiguous, and simple. Reliability test showed acceptable a values of at least 0.70 for each domain, suggesting that the questionnaire was reliable. Conclusion: This tool could be considered valid and reliable for assessing the level of KAP towards salt intake among adults in Malaysia.